Evolutionary history of herbivory in the Patagonian steppe: The role of climate, ancient megafauna, and guanaco - Hernandez, Fidel; Rios Cardoza, Carlos Francisco; Perotto-Baldivieso, Humberto L. (My University, 2019)
Herbivory is an important ecological process than has influenced the evolution of grassland-savannah systems. The evolutionary history of herbivory largely determines how resilient plant communities are to herbivory, with communities evolving with a long history generally possessing plant adaptations that make them able to cope with such disturbance. Thus, the evolutionary history of herbivory can serve as an indicator of a system's resilience to modern grazing. Determining this history, however, is problematic because quantitative measures of herbivory and knowledge of plant origin are needed over appropriate evolutionary time frames. Paleoecology offers a useful framework for assessing this evolutionary history of plant-herbivore interactions. The Patagonian steppe is a phytogeographic province of South America whose evolutionary history of herbivory has been debated. Past discussions have focused completely on the abundance of its sole large ungulate herbivore-the guanaco (Lama guanicoe Muller 1776)-since European colonization of the continent. Here we use a paleoecological approach to reconstruct the evolutionary history of herbivory and plant evolution in the Patagonian steppe over a much broader, geologic time frame (Cenozoic) to shed light on the matter. We examine the role of past climate, ancient megafauna, and guanaco in shaping the vegetation and briefly discuss how present land use may be misaligned with the steppe's evolutionary history of herbivory. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: evolutionary history of herbivory; grazing; guanaco; late-pleistocene extinction; megafauna; patagonian steppe